Early introduction of complementary foods/drinks and milk feeding type in the Special Supplemental Nutrition Program for Women, Infants and Children (WIC) - Kristin J. Marks; Ellen O. Boundy; Jasmine Y. Nakayama; Ruowei Li; Heather C. Hamner (Wiley, 2023)
Abstract Infants younger than 4 months are not ready for complementary foods/drinks (any solid or liquid other than breast milk or infant formula). Almost half of US infants participate in the Special Supplemental Nutrition Program for Women, Infants and Children (WIC), which provides nutrition education and support to low‐income families. We describe the prevalence of early introduction (<4 months) of complementary foods/drinks and examine the association of milk feeding type (fully breastfed, partially breastfed or fully formula fed) with early introduction of complementary foods/drinks. We used data from 3310 families in the longitudinal WIC Infant and Toddler Feeding Practices Study‐2. We described the prevalence of early introduction of complementary foods/drinks and modeled the association of milk feeding type at Month 1 with early introduction of complementary foods/drinks using multi‐variable logistic regression. Thirty‐eight percent of infants were introduced early to complementary foods/drinks (<4 months). In adjusted models, infants who were fully formula fed or partially breastfed at Month 1 were 75% and 57%, respectively, more likely to be introduced early to complementary foods/drinks compared with fully breastfed infants. Almost two in five infants were given complementary foods/drinks early. Formula feeding at Month 1 was associated with higher odds of early introduction of complementary foods/drinks. There are opportunities to support families participating in WIC to prevent early introduction of complementary foods/drinks and promote child health.